The application of autologous serum eye drops in severe dry eye patients; subjective and objective parameters before and after treatment - Jirsova, Katerina; Brejchova, Kristyna; Krabcova, Ivana; Filipec, Martin; Al Fakih, Aref; Palos, Michalis; Vesela, Viera (Current eye research, 2014)
AIM: To assess the impact of autologous serum (AS) eye drops on the ocular surface of patients with bilateral severe dry eye and to draw a comparison between the clinical and laboratory examinations and the degree of subjective symptoms before and after serum treatment. MATERIALS AND METHODS: A three-month prospective study was conducted on 17 patients with severe dry eye. AS eye drops were applied a maximum of 12 times a day together with regular therapy. Dry eye status was evaluated by clinical examination (visual acuity, Schirmer test, tear film breakup time, vital staining, tear film debris and meniscus), conjunctival impression cytology (epithelial and goblet cell density, snake-like chromatin, HLA-DR-positive and apoptotic cells) and subjectively by the patients. RESULTS: The application of AS eye drops led to a significant improvement in the Schirmer test (p < 0.01) and tear film debris (p < 0.05). The densities of goblet (p < 0.0001) and epithelial cells (p < 0.05) were significantly increased, indicating a decrease of squamous metaplasia after AS treatment. A significant decrease (p < 0.05) was found in the number of apoptotic, HLA-DR-positive and snake-like chromatin cells on the ocular surface. A significant improvement was found in all evaluated subjective symptoms. Altogether, the clinical results were improved in 77%, the laboratory results in 75% and the subjective feelings in 63% of the eyes. CONCLUSIONS: We found that three-month AS treatment led especially to the improvement of ocular surface dryness and damage of the epithelium. The improvement of dry eye after AS treatment correlated well with the clinical, laboratory and subjective findings. From the patients' subjective point of view, the positive effect of AS decreased with time, but still persisted up to three months after the end of therapy.
Keywords: syndromy suchého oka; Epithelium, Corneal; oční roztoky; Patient Satisfaction; Humans; lidé středního věku; Dry Eye Syndromes; Female; Aged; dospělí; výsledek terapie; senioři; lidé; spokojenost pacientů; zrakové testy; Adult; rohovkový epitel; ženské pohlaví; Goblet Cells; Ophthalmic Solutions; stupeň závažnosti nemoci; Male; Middle Aged; Treatment Outcome; pohárkové buňky; Severity of Illness Index; mužské pohlaví; prospektivní studie; Visual Acuity; zraková ostrost; Vision Tests; Prospective Studies